Search for B+→ π+ and B0→ π0 decays - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2006)
A search has been made for the decays B+→ π+ and B0→ π0 in a data sample of approximately 232×106 BB̄ pairs recorded at the Υ(4S) resonance with the BABAR detector at the PEP-II B-meson Factory at SLAC. No significant signals have been observed, and therefore upper limits have been set on the branching fractions: B(B+→ π+)<2.4×10-7 and B(B0→ π0)<2.8×10-7 at 90% probability. © 2006 The American Physical Society.